FAKTOR-FAKTOR YANG MEMPENGARUHI KEANDALAN PELAPORAN KEUANGAN PADA PEMERINTAHAN DESA DI KECAMATAN PAPAR KABUPATEN KEDIRI - Suwandari, Anggie Yuna (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to find out whether there is a partial influence between human resources, the use of information technology, and internal control on the reliability of financial reporting in village government in the district of Kediri. And is there a simultaneous influence between human resources, the use of information technology, and internal control on the reliability of financial reporting in the village government in the sub-district of the district of Kediri. In this research method using multiple linear regression. The results of this study partially human resource capacity variables significantly influence the reliability of financial reporting and the variable utilization of information technology and internal control partially does not significantly affect the reliability of financial reporting. For the simultaneous test, namely the capacity of human resources, the use of information technology and internal control simultaneously have a significant effect on the reliability of financial reporting.